Clinical and Radiological Approach to the Diagnosis of Branch Atheromatous Disease: Case Report and Review of Literature - Prianto, Johanna Tania; Achmad Bayhaqi; Mohd Fandi Al-Khafiz Kamis; Rajeev Shamsuddin Perisamy; Mohammad Syafeeq Faeez Md Moh (Journal Of Cardiovascular, Neurovascular & Stroke, 2025)
Branch atheromatous disease (BAD) is a subtype of ischemic stroke caused by stenosis or occlusion at the entrance of the penetrating branch due to the presence of plaque. Despite its clinical importance, this concept is understudied and not commonly used in clinical and research settings. BAD is highly associated with high early neurological deterioration (END) and disability. There are several characteristics of BAD based on clinical condition, risk factors, laboratory results, and most importantly, radiographic features of infarct and blood vessels morphologies, also associated features. Early diagnosis of BAD is critical for determining treatment decisions and the prognosis of individual patients.